E-Pocket note: an interactive video learning for effective online teaching and learning process / Norhayati Zamri ... [et al.] - Zamri, Norhayati; Omar, Nor Bahiyah; Mansor, Norul Akma; Ab Rahman, Liyana; Mohd Fatzel, Farah Husna (2021)
The COVID-19 outbreak had significantly impacted our daily lives since the year 2020, forcing the Malaysian government to restructure many sectors, including the education system. As a result of the pandemic, Malaysia's education system has made a rapid transition from face-to-face to open and distance learning (ODL) classes. This situation brings greater challenges for teachers, they need to find a better method to teach students effectively, especially during online classes. Therefore, the objective of this study is aimed at creating an interactive video learning that we called an e-Pocket Note for students’ use during the online learning process. This application contains a set of interactive videos together with questions and answers related to certain topics that will enhance students' understanding. A survey has been distributed among the students to know their perception regarding the use of video as one of the teaching methods. The results showed that there is a need for the use of interactive videos during the ODL classes. Thus, the use of the e-Pocket Note application is compatible with the recent educational situation. It also allows for increased student motivation to learn as well as improved student-teacher engagement, which leads to an effective teaching and learning process.